Konsep Ilmu Dan Pendidikan Dalam Persfektif Surat Al-Mujadilah Ayat 11 - Ahmad Fahrudin; Arbaul Fauziah (IAIN Tulungagung, 2020)
Abstract Education is one of the main things that can make a significant contribution to the development and progress of a nation. This fact is evidenced by the existence of a generation of people who are quality-produced from educational institutions in Indonesia, if the young generation of this nation does not attend education, perhaps the development and progress of the times will not be able to be like today. Education, especially in Muslims, one of the foundations and guidelines for which is the Koran, through some of the verses it contains, there are some instructions and knowledge that are very extraordinary if we dig into the meaning for the meaning. So it is important for Muslims to make Al-Qur'an as a guide in processing their studies. Education and knowledge are two main things that are interrelated, they are like two sides of a coin that cannot be separated, even always in pairs. In the context of this article, the concept of knowledge and education from the perspective of the Koran will be discussed, namely taking one of the verses in Surah al-Mujadilah, verse 11. The verse explains the various things it contains, then explains Asbabun Nuzul, describes the verse, Menafsiri is then analyzed, hopefully, what is discussed here becomes a study that can increase wealth, both theoretical wealth and scientific wealth practically. Keywords: Science, Education, Al-Mujadilah. Abstrak Pendidikan merupakan salah satu perkara pokok yang mampu memberikan kontribusi signifikan terhadap perkembangan dan kemajuan suatu bangsa. Fakta ini dibuktikan dengan adanya generasi bangsa yang secara kualitas dihasilkan dari bangku lembaga pendidikan yang ada di Indonesia, jika generasi muda bangsa ini tidak mengenyam bangku pendidikan, mungkin perkembangan dan kemajuan zaman tidak mampu seperti sekarang ini. Pendidikan khususnya dalam umat Muslim, salah satu landasan dan yang menjadi pedomannya adalah al-Qur’an, melalui beberapa ayat yang dikandungnya, terdapat beberapa petunjuk dan ilmu yang sangat luar jika diselami makna demi maknanya. Maka menjadi penting bagi umat Muslim menjadikan al-Qur’an sebagai pegangan dalam berproses di dalam menuntut ilmu. Pendidikan dan ilmu merupakan dua hal pokok yang berkaitkelindan, keduanya ibarat dua sisi mata uang logam yang tak mampu dipisahkan, bahkan selalu berpasangan. Dalam konteks artikel ini, maka akan di bahas kosep ilmu dan pendidikan dari persfektif al-Qur’an, yaitu mengambil salah satu ayatnya dalam surat al-Mujadilah ayat 11. Ayat tersebut dijelaskan berbagai hal yang dikandungnya, kemudian dijelaskan asbabun nuzul, mendeskripsikan ayat, menafsiri kemudian dianalisis, semoga apa yang dibahas di sini menjadi sesuatu kajian yang mampu menambah kekayaan, baik kekayaan secara teoritis maupun kekayaan keilmuan secara praktis. Kata Kunci: Ilmu, Pendidikan, Al-Mujadilah.